Influence of natural plantations with participance of velvetweed oak on soil fertility - Rafalska, L. P. (Землеустрій, кадастр і моніторинг земель, 2017)
According to research in natural 31‐167 annual overgrown plantationsof velvetweed oak established that in soil of mixed forest plantation more humusand nitrogen compared with pure. On the content of phosphorusand potassium certain regularity was not found.